2020
DOI: 10.20870/oeno-one.2020.54.4.3863
|View full text |Cite
|
Sign up to set email alerts
|

Vine performance benchmarking of indigenous Cypriot grape varieties Xynisteri and Maratheftiko

Abstract: Aim: The aims of this study were to (1) formulate a baseline understanding of the performance of the indigenous Cypriot white grape Xynisteri and the red grape Maratheftiko (Vitis vinifera L.), and (2) compare these varieties to Shiraz and Sauvignon blanc grown in a Cypriot vineyard.Materials and results: The investigation involved multiple dry grown vineyards from the Krasochoria region of Lemesos, Cyprus, during the 2017, 2018 and 2019 vintages. Vine performance measurements, including midday stem water pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 73 publications
12
5
0
Order By: Relevance
“…XP and MP had the largest shoot diameter and MP had the longest internode length with SBA the shortest (Table 3). These findings are consistent with the field trial data from Copper et al, (2020) where Xynisteri had the longest shoots and the largest shoot diameter and Maratheftiko had the least leaves per shoot and longest internode length.…”
Section: Potted Vine Trialssupporting
confidence: 90%
See 2 more Smart Citations
“…XP and MP had the largest shoot diameter and MP had the longest internode length with SBA the shortest (Table 3). These findings are consistent with the field trial data from Copper et al, (2020) where Xynisteri had the longest shoots and the largest shoot diameter and Maratheftiko had the least leaves per shoot and longest internode length.…”
Section: Potted Vine Trialssupporting
confidence: 90%
“…While the results for 2020/21 were not conclusive, findings for 2019 were similar to those reported by Copper et al, (2020) who demonstrated that Xynisteri had higher stem water potential than Maratheftiko and Shiraz, while Sauvignon Blanc had the lowest stem water potential. Water potential has been widely used as an indicator of plant water status for irrigation management purposes (García-Tejera et al, 2021).…”
Section: Potted Vine Trialssupporting
confidence: 81%
See 1 more Smart Citation
“…It is to be expected that both cultivars have different mechanisms to cope with drought stress. The native cultivar Xynisteri is well-adapted to drought [ 45 , 46 ], while the drought-sensitive cultivar Chardonnay [ 32 ], which originates from French valleys with humid conditions, probably lacks adaptations to quickly cope with drought stress [ 45 ]. The higher basal activity of antioxidant enzymes (POD and SOD) and the higher basal levels of proline in Xynisteri may be part of its basal toolset to cope with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Xynisteri and Chardonnay covered 30.2% and 1.6% of the circa 6142 ha viticultural area of Cyprus, respectively [ 8 ]. The clone of Chardonnay is unknown and, to our knowledge, no clones of Xynisteri have been identified [ 46 ]. Sixty self-rooted cuttings of each cultivar were planted in 8-litre polyethylene pots containing soil originating from the traditional vineyard area in Limassol.…”
Section: Methodsmentioning
confidence: 99%